2018
DOI: 10.1101/305698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directional coupling of slow and fast hippocampal gamma with neocortical alpha/beta oscillations in human episodic memory

Abstract: Episodic memories hinge upon our ability to process a wide range of multisensory information and bind this information into a coherent, memorable representation. On a neural level, these two processes are thought to be supported by neocortical alpha/beta desynchronisation and hippocampal theta/gamma synchronisation, respectively. Intuitively, these two processes should couple to successfully create and retrieve episodic memories, yet this hypothesis has not been tested empirically. We address this by analysing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Changes in gamma synchronization would then reflect changes in information processing, including endogenously-generated states. Hence, alterations in gamma synchronization may well contribute to changes in processes like autobiographical memory retrieval 193 and awareness of one’s own internal state during the psychedelic experience 194 195 .…”
Section: Effects Of Psychedelics On Brain Network Integrationmentioning
confidence: 99%
“…Changes in gamma synchronization would then reflect changes in information processing, including endogenously-generated states. Hence, alterations in gamma synchronization may well contribute to changes in processes like autobiographical memory retrieval 193 and awareness of one’s own internal state during the psychedelic experience 194 195 .…”
Section: Effects Of Psychedelics On Brain Network Integrationmentioning
confidence: 99%
“…Probing rat hippocampal neurons in vitro, Bi and Poo () showed that the postsynaptic neuron must fire 20 ms (that is, 1 cycle of a gamma oscillation) after the presynaptic neuron to induce LTP. Given that these hippocampal neurons have been shown to lock gamma‐band activity (Jutras, Fries, & Buffalo, ) and hippocampal gamma‐band activity is predictive of memory formation (e.g., Griffiths et al, ; Long & Kahana, ), one could speculate that increases in the amplitude of hippocampal gamma oscillations reflect increases in STDP.…”
Section: A Role For Neural Oscillationsmentioning
confidence: 99%
“…confidence rating = 1). While earlier studies using this paradigm 23,35 have only considered 'highly confident' memories (i.e. max confidence rating), we chose a more lax confidence threshold to ensure that sufficient trials of each dynamic stimulus available for the fMRI representational similarity analysis.…”
Section: Behavioural Analysismentioning
confidence: 99%